2021
DOI: 10.1155/2021/5623650
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Damage and Failure of Coal-Pillar Dams in Coal Mine Underground Reservoir under Dynamic Load

Abstract: The stability of coal-pillar dams in underground hydraulic engineering works is affected not only by long-term water erosion but also by dynamic loading induced, for example, by roof breaking or fault slipping. In this paper, the water absorption characteristics of coal samples from western China were studied by nondestructive immersion tests, and a high-speed camera was used to monitor SHPB tests on samples of varying water content and subjected to various strain rates. Besides, the coal-pillar dam is numeric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 23 publications
2
10
0
Order By: Relevance
“…Experimental research is an important method for studying waterproof coal pillars (Chen et al 2022b). Currently, experimental investigations on waterproof coal pillars primarily focus on the weakening effects of water content on the mechanical parameters of coal samples (Yao et al 2021b). Yao et al (2020) conducted tests involving variable-angle shear on coal samples with different water contents, while (Lu et al 2016;Wang et al 2018;Zhang and Nie 2020) performed uniaxial and triaxial tests on coal samples with varying water contents.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental research is an important method for studying waterproof coal pillars (Chen et al 2022b). Currently, experimental investigations on waterproof coal pillars primarily focus on the weakening effects of water content on the mechanical parameters of coal samples (Yao et al 2021b). Yao et al (2020) conducted tests involving variable-angle shear on coal samples with different water contents, while (Lu et al 2016;Wang et al 2018;Zhang and Nie 2020) performed uniaxial and triaxial tests on coal samples with varying water contents.…”
Section: Introductionmentioning
confidence: 99%
“…Based on field experience and numerical model studies, Mathey et al [24] proposed another South African squat coal pillar strength formula. Combined with numerical simulation research, Yao et al [25] monitored coal samples with different water contents and strain rates through a non-destructive immersion test, which is significant for the design of the water-resisting coal pillar.…”
Section: Introductionmentioning
confidence: 99%
“…Recent years has witnessed extensive researches on the mechanical properties of coal rock under water interaction. For varying-MC coal rock samples (i.e., coal rock samples that contain varying contents of moisture), the quantitative relation between MC and macroscopic mechanical parameters (such as cohesion, elastic modulus, internal friction angle and uniaxial compressive strength) was obtained in uniaxial compression tests (Erguler and Ulusay, 2009; Hawkins and McConnell, 1992; Song et al., 2022; Yang et al., 2018; Yao et al., 2016) and shear tests (Li et al., 2020; Yao et al., 2020, 2021). It was found that the peak stress, internal friction angle, cohesion and elastic modulus decrease with the rise of MC; meanwhile, the tensile failure mode alters to the shear failure mode (Tang, 2018; Tang et al., 2021).…”
Section: Introductionmentioning
confidence: 99%